Social Networks Help Control Hypertension. Issue 1 (26th November 2012) - Shaya, Fadia T.; Chirikov, Viktor V.; Daniel Mullins, C.; Shematek, Jon; Howard, DeLeonardo; Foster, Clyde; Saunders, Elijah
<x xml:space="preserve">Abstract</x> Cardiovascular health disparities continue to pose a major public health problem. The authors evaluated the effect of education administered within social networks on the improvement of hypertension in 248 African Americans compared with historical controls. Patients formed clusters with peers and attended monthly hypertension education sessions. The authors assessed the likelihood of reaching goal below predefined systolic blood pressure (SBP) and diastolic blood pressure (DBP) thresholds as well as the absolute reduction in SBP and DBP, controlling for diabetes, smoking, baseline hypertension, and demographics. The intervention group was more likely to have ever reached treatment goal at 12‐month follow‐up (odds ratio, 1.72; P=.11). At 18‐month follow‐up, the Maryland Cardiovascular Disease Promotion Program group had a statistically significant larger drop in SBP (−4.82 mm Hg, P<.0001) and DBP (−3.37 mm Hg, P=.01) than the control group. The clustering of patients in social networks around hypertension education has a positive impact on the management of hypertension in minority populations and may help address cardiovascular health disparities.